Regional comparison of dietary intakes and health related behaviors among residents in Asan - Kim, Ji-Sun (The Korean Nutrition Society and The Korean Society of Community Nutrition, 2007)
Inadequate dietary intakes and poor health behaviors are of concern among rural residents in Korea. This study is conducted to compare dietary intakes, dietary diversity score (DDS), mean nutrient adequacy ratio (MAR) and health related behaviors by rural, factory and urban areas in Asan. A total of 930 adults (351 men and 579 women) were interviewed to assess social economic status (SES), health related behaviors and food intakes by a 24-hour recall method. Mean age was 61.5 years with men being older (64.8 years) than women (59.3 years, p<0.001). Men in the factory area were older than rural or urban men while urban women were the youngest. Education and income of urban residents were higher than other area residents. There were more current drinkers in urban area while smoking status was not different by regions. Physical activity was significantly higher in rural or factory areas, whilst urban residents exercised more often (p<0.05). Rural or factory area residents considered themselves less healthy than others while perceived stress was lower than urban residents. Energy intakes were higher in urban residents or in men, however, after SES was controlled, energy intake did not show any differences. Energy-adjusted nutrient intakes were significantly higher in the urban area (p<0.05) for most nutrients except for carbohydrate, niacin, folic acid, vitamin B(6), iron and fiber. Sodium intake was higher in factory area than in other areas after SES was controlled. DDS of rural men and MAR of both men and women in the rural area were significantly lower when SES was controlled. In conclusion, dietary intakes, diversity, adequacy and perceived health were poor in the rural area, although other health behaviors such as drinking and perceived stress were better than in the urban area. In order to improve perceived health of rural residents, good nutrition and exercise education programs are recommended.